PENGARUH PENGUNGKAPAN INFORMASI PROYEKSI DAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KOEFISIEN RESPON LABA - Indarti Diah Palupi; Diah Ayu Wulandari; Dyah Ayu Safitri (Universitas Muhammadiyah Surakarta, 2017)
Since many corporate’s disclosures are claimed to be more value relevant and more informative, this research examines if the earnings response coefficient changes by projections and corporate social responsibility (CSR) disclosures. Data were obtained from companies incorporated in the LQ 45, August 2014 - January 2015 period. This research used two models, model 1 (without control variables) and model 2 (with control variables) that test using Ordinary Least Squares Regression. On model 1, the F test results indicate that projections and CSR disclosures simultaneously have significant effect on the ERC. While the t test results showed that partially, projections have negative significant effect on ERC. This results reflect that diclosure of projections aim to lower asimmetry information because of corporate’s prospect uncertainty. CSR disclosures have no significant effect on ERC but the coefficient was negative, according to the research hypothesis. On model 2, both the F test and t test results showed that the projection information, CSR, capital structure, and company growth simultaneously and partially have no significant effect on the ERC. Keywords: projections, corporate social responsibility, earning respon coefficient